2007
DOI: 10.1002/ijc.23107
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Immunotherapy of metastatic breast cancer patients with vitamin D‐binding protein‐derived macrophage activating factor (GcMAF)

Abstract: The above article from the International Journal of Cancer, published online on 12 October 2007 in Wiley Online Library and in Volume 122, Issue 2, pp 461–467, has been retracted by agreement between the journal Editor‐in‐Chief Peter Lichter and Wiley Periodicals, Inc. due to irregularities in the documentation for institutional review board approval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 50 publications
4
73
1
Order By: Relevance
“…VDBP is involved in calcium homeostasis, immunity (21,22), and antiangiogenic (23) as well as antiproliferation processes (24). The protein is primarily synthesized in the liver and secreted into the plasma, where it binds to vitamin D and known to be taken up by human mammary cells via endocytosis (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDBP is involved in calcium homeostasis, immunity (21,22), and antiangiogenic (23) as well as antiproliferation processes (24). The protein is primarily synthesized in the liver and secreted into the plasma, where it binds to vitamin D and known to be taken up by human mammary cells via endocytosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to immunity, VDBP is involved in macrophage activation by having its branched trisaccharide complex hydrolyzed by b-glactosidase on B cells and salidase from T cells forming the macrophage activating factor (GcMAF). In patients with metastatic breast cancer it was found that administration of VDBP in the form of GcMAF decreased Nagalase activity, an indicator of macrophage activation that can lead to cancer cell death (21).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Molecularly, GcMAF is thought to be DBP with a single terminal O-linked GalNAc sugar residue. [4][5][6][7] In its native molecular state, DBP is a mixture of posttranslationally unmodified (except for disulfide bonds) and O-glycosylated species, the glycosidic degree and nature of which depends on DBP genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Although GcMAF therapy has been found to show curative effects on a variety of cancers (10-13,37,38), Yamamoto et al stated that the efficacy of GcMAF therapy for a variety of cancer types depends on the degree of cell membrane abnormality (12,13). Undifferentiated tumor cells are killed more efficiently than differentiated tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Highly activated macrophages have been reported to have a tumoricidal potential (6)(7)(8)(9). Pilot studies have reported the efficacy of GcMAF-based immunotherapy of metastatic cancer in animal and humans (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%